Hydrogen economy supply chain, life cycle analysis and energy transition for sustainability - Scipioni, Antonio; Manzardo, Alessandro; Jingzheng, Ren (Academic Press, 2017)
Hydrogen Economy: Supply Chain, Life Cycle Analysis and Energy Transition for Sustainability explores the challenges for the transition into a sustainable hydrogen economy. In this book, experts from various academic backgrounds discuss the tools and methodologies for the analysis, planning, design and optimization of hydrogen supply chains. They examine the available technologies for hydrogen production, storage, transport, distribution and energy conversion, providing a cross cutting perspective on their sustainability. Environmental, social and economic aspects are considered, allowing for a more complete life cycle assessment of the entire supply chain. Methods and frameworks for multi-criteria decision making for the sustainable implementation of hydrogen systems are also covered. Providing a broad overview of the subject and well-recognized tools to manage hydrogen sustainability, this book is a useful resource for engineering researchers and PhD students in energy, environmental and industrial areas, energy economy researchers, practicing hydrogen energy engineers and technicians, energy and environmental consultants, life cycle assessment practitioners and consultants.--Provided by publisher.